An attempt to find the correlation between various flexibility tests - Ettling, I. E. L.(Iris Elizabeth Louie) (Stellenbosch : Stellenbosch University, 2012)
Treatise (B. Ed. Ph.) -- University of Stellenbosch, 1943.